2011
DOI: 10.1128/jb.00085-11
|View full text |Cite
|
Sign up to set email alerts
|

Age of Inoculum Strongly Influences Persister Frequency and Can Mask Effects of Mutations Implicated in Altered Persistence

Abstract: The majority of cells transferred from stationary-phase culture into fresh medium resume growth quickly, while a few remain in a nongrowing state for longer. These temporarily nonproliferating bacteria are tolerant of several bactericidal antibiotics and constitute a main source of persisters. Several genes have been shown to influence the frequency of persisters in Escherichia coli, although the exact mechanism underlying persister formation is unknown. This study demonstrates that the frequency of persisters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
164
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 48 publications
(88 reference statements)
16
164
1
Order By: Relevance
“…As evidence that the sedimented cells are persisters, Keren and colleagues performed LIVE/DEAD (SYTO/ PI) staining to show that all remaining cells stained as live cells (15). However, the claim that these sedimented cells are all persisters has come under scrutiny due to additional studies that have demonstrated that cell lysis by ␤-lactams leaves many more cells with intact membranes than there are persisters in the population (7,12,21). Here, we sought to determine if ␤-lactam lysis would be useful for isolation of wild-type E. coli persisters for metabolic measurements.…”
Section: Ampicillin-lysed Cultures Include More Vbncs Than Persistersmentioning
confidence: 99%
“…As evidence that the sedimented cells are persisters, Keren and colleagues performed LIVE/DEAD (SYTO/ PI) staining to show that all remaining cells stained as live cells (15). However, the claim that these sedimented cells are all persisters has come under scrutiny due to additional studies that have demonstrated that cell lysis by ␤-lactams leaves many more cells with intact membranes than there are persisters in the population (7,12,21). Here, we sought to determine if ␤-lactam lysis would be useful for isolation of wild-type E. coli persisters for metabolic measurements.…”
Section: Ampicillin-lysed Cultures Include More Vbncs Than Persistersmentioning
confidence: 99%
“…Persister cells may have morphologies indistinguishable from those of susceptible cells or be distinct in some way, e.g., coccoid shape in old cultures and biofilms or cell wall-defective L-forms (85). The concept of persisters has evolved from the presumed homogeneous persister population (8) to much more heterogeneous and diverse populations (40,43,44,83) that are defined by specific conditions. Persisters are likely to comprise different subpopulations (40,44,83) and generally form a small and relatively predictable proportion of a culture.…”
Section: What Are Persisters?mentioning
confidence: 99%
“…Clinically, persisters have been found to be important to the pathogenesis of infections, including persistent tuberculosis, reoccurring uropathogenic E. coli infections, and Pseudomonas aeruginosa infections in cystic fibrosis patients (10)(11)(12)(13)(14). The rate of persister formation is much higher in stationary-phase cells than in actively growing cells (10,(15)(16)(17)(18)(19). In addition to increasing rates of persister formation, stationary phase can also increase rates of resistance and tolerance to antibiotics (18,(20)(21)(22)(23).…”
mentioning
confidence: 99%